2011
DOI: 10.1038/emboj.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interkinetic nuclear migration by cell cycle-coupled active and passive mechanisms in the developing brain

Abstract: Regulation of interkinetic nuclear migration by cell cycle-coupled active and passive mechanisms in the developing brainIn proliferating neural epithelia, cells undergo interkinetic nuclear migration: stereotyped cell cycle-dependent movements in the apico-basal plane. The microtubule-binding protein Tpx2 is here shown to regulate the G2-phase basal-to-apical migration, while passive displacement effects are responsible for basally directed movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
211
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(222 citation statements)
references
References 54 publications
11
211
0
Order By: Relevance
“…It has been speculated that this may be a way of increasing the density of precursor cells while maintaining adherens junctions during mitosis (Frade 2002). In support of this view, it has been observed that migration towards the basal side of the VZ occurs in a passive manner due to migration of nuclei at the G2/M phase towards the apical side (Kosodo et al 2011). An additional option is that this movement allows differential exposure to environmental cues that differ in the apical (mitotic) versus the basal (neurogenic) domains.…”
Section: Interkinetic Nuclear Movementssupporting
confidence: 51%
See 2 more Smart Citations
“…It has been speculated that this may be a way of increasing the density of precursor cells while maintaining adherens junctions during mitosis (Frade 2002). In support of this view, it has been observed that migration towards the basal side of the VZ occurs in a passive manner due to migration of nuclei at the G2/M phase towards the apical side (Kosodo et al 2011). An additional option is that this movement allows differential exposure to environmental cues that differ in the apical (mitotic) versus the basal (neurogenic) domains.…”
Section: Interkinetic Nuclear Movementssupporting
confidence: 51%
“…The microtubule-associated protein Tpx2 may be involved in microtubule assembly in a cell cycle-specific manner. By redistribution in a cell cycle-dependent manner and an effect on microtubule organization, Tpx2 couples cell cycle and interkinetic nuclear movement (Kosodo et al 2011). Tpx2 begins to be expressed in S phase and accumulates in the nucleus.…”
Section: Molecular Motors and The Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many basal nuclear migrations during G1/S phase are passive, cell non-autonomous movements, during which G1/S nuclei are forced basally when G2 nuclei of neighboring cells actively migrate apically and, therefore, push G1/S nuclei out of the apical regions (Fig. 3A) (Kosodo et al, 2011). LINC-independent mechanisms that underlie apical movements during G2 are better understood.…”
Section: Nuclear Migration In Developing Epitheliamentioning
confidence: 99%
“…The nuclei of progenitors move between the apical and basal surfaces of the neuroepithelium in phase with their cell cycle, a process termed interkinetic nuclear migration (INM), which may have a role in regulating cell cycle and proliferation [Del Bene et al, 2008]. During INM, the plus end-directed motor dynein and the minus end-directed motor kinesin are required for apical and basal migration of the nucleus, respectively [Tsai et al, 2010;Kosodo et al, 2011].…”
Section: Epithelial Cell Polarizationmentioning
confidence: 99%